Sphingosine 1‐phosphate/microRNA‐1249‐5p/MCP‐1 axis is involved in macrophage‐associated inflammation in fatty liver injury in mice. Issue 11 (13th August 2020) - Ji, Xiaofang; Yang, Le; Zhang, Zhi; Zhang, Kai; Chang, Na; Zhou, Xuan; Hou, Lei; Yang, Lin; Li, Liying
Abstract: Monocyte chemotactic protein‐1 (MCP‐1) is one of the most representative inflammatory cytokines, and has been proved to be markedly increased in injured liver and sphingosine 1‐phosphate (S1P)‐treated macrophages. However, microRNAs (miRNAs) targeting MCP‐1 and the role of miRNA/MCP‐1 axis in S1P‐mediated liver inflammation remain largely unknown. Here, we demonstrate that MCP‐1 expression is increased in the liver and isolated liver macrophages of MCDHF mice. Moreover, there is a positive correlation between the hepatic levels of S1P and MCP‐1. We then predict miRNAs targeting MCP‐1 by bioinformatics analysis and select miRNA‐1249‐5p (miR‐1249‐5p) from the intersection of TargetScan database and downregulated miRNAs in the injured liver. S1P significantly upregulates the expression of MCP‐1 and decreases miR‐1249‐5p expression in macrophages. MiR‐1249‐5p directly targets 3'‐UTR of MCP‐1 and negatively regulates its expression in S1P‐treated macrophages. Administration of miR‐1249‐5p agomir decreases hepatic MCP‐1 levels and attenuates liver inflammation in MCDHF mice. Protein‐protein interaction network by STRING displays that S1P system is closely associated with MCP‐1/CCR2 axis in the network of inflammation. In conclusion, we characterize the vital role of miR‐1249‐5p in negatively regulating MCP‐1 expression in vitro and in vivo, which may open new perspectives for pharmacological treatment of liver disease. Abstract : S1P upregulates the expression of MCP‐1 and downregulates miR‐1249‐5p expression in macrophages, miR‐1249‐5p targeting MCP‐1 negatively regulates MCP‐1 expression in S1P‐treated macrophages. MCP‐1 expression is increased in the liver and isolated liver macrophages of MCDHF mice, S1P/miR‐1249‐5p axis governs macrophage MCP‐1 expression and macrophage‐associated inflammation during liver injury.